2018
DOI: 10.3758/s13420-018-0323-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral synchronization and affiliation: Dogs exhibit human-like skills

Abstract: Behavioral synchronization is evolutionary adaptive, fostering social cohesion. In humans, affiliation between partners is associated with a high level of behavioral synchronization; people show increased affiliation towards people who synchronize with them. Surprisingly, until recently, little was known about these phenomena at an interspecific level, which is, however, essential to better understand the respective roles of evolution and ontogeny. After presenting why dog-human dyads are a relevant biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 80 publications
1
20
1
Order By: Relevance
“…Sharing spaces in the context of a human-dog relationship is essential, as they are both social species. Several studies have been published on dog social cognition, focusing on behavioral synchronization in the dog-human dyad [ 55 , 56 , 57 ]. The dog that daily shares life with human beings acquires cognitive and social skills in relation to the dimensions of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing spaces in the context of a human-dog relationship is essential, as they are both social species. Several studies have been published on dog social cognition, focusing on behavioral synchronization in the dog-human dyad [ 55 , 56 , 57 ]. The dog that daily shares life with human beings acquires cognitive and social skills in relation to the dimensions of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the existence of behavioural synchronization between dogs and humans (see for review [ 45 ]). The canine synchronizes its locomotor behaviour with that of its owner in different contexts, both indoors [ 46 ] and outdoors [ 47 ], and when facing an unfamiliar human.…”
Section: Visual Communicationmentioning
confidence: 99%
“…It has also been reported that the behavioural synchronization phenomenon is affected by dogs’ affiliation toward humans; pet dogs show a higher performance in synchronizing their behaviour with their owner’ than shelter dogs with their caregivers. Moreover, behavioural synchronization affects dogs’ social preference toward humans, and in particular, toward individuals synchronizing their locomotor activity with them [ 45 ]. Thus, authors concluded that, as previously described in humans, this phenomenon increases social cohesion and affiliation in dog–human dyads, contributing to emotional contagion [ 49 ].…”
Section: Visual Communicationmentioning
confidence: 99%
“…That could lead to keeping the dog out if it was deemed too high risk, warning the handler so they can be prepared or use a distraction technique on the dog, move the dog so there is lower risk to it or to the patient if the dog reacts (e.g., jumps). If the dog handler becomes stressed for whatever reason during a treatment session, he or she should leave the dental clinic operatory together with the dental therapy dog. Dogs can very easily recognise stress amongst humans and will synchronise their behaviour accordingly and especially with the dog owner (Duranton & Gaunet, ). The dog handler's role is to prevent, recognise, and manage any stress‐associated behaviour, and he or she must consistently work to influence the dog's perception of the environment and minimise stress responses, for example, by mental stimulation. This interaction has been described as social synchrony between the dog handler and the animal (Pirrone, Ripamonti, Garoni, Stradiotti, & Albertini, ).…”
Section: Resultsmentioning
confidence: 99%